Perceived Family Functioning Profile in Adolescents at Clinical High Risk for Psychosis: Rigidity as a Possible Preventive Target - Iorio, Melanie; Casini, Erica; Damiani, Stefano; Fusar-Poli, Paolo; Borgatti, Renato; Mensi, Martina Maria, Clinical High Risk State for Psychosis Research Group (Frontiers in Psychiatry, 2022)
The presence of a positive family relationship has been suggested as a protective factor from parental stress and from the development of full-blown psychosis. However, to date, there is limited research on family functioning in adolescents with psychosis and at clinical high risk for psychosis (CHR-P). This study aims at comparing family functioning and perceived stress in parents of adolescents with either CHR-P, early onset psychosis (EOP) or other psychiatric disorders (no CHR-P). As a secondary aim, it will correlate family functioning with parental perceived stress in order to find critical targets of intervention. We conducted a RECORD-compliant, real-world, cross-sectional study. One-hundred-eleven adolescents aged 12-17 accessing the IRCCS Mondino Foundation Neuropsychiatric services (Pavia, Italy) between 2017 and 2020 and their parents (n=222) were included. Sociodemographic characteristics of adolescents and their parents were collected. Family functioning was evaluated through the Family Adaptability and Cohesion Evaluation Scale-IV (FACES-IV) and the level of stress through the Perceived Stress Scale (PSS). Twenty adolescents had EOP, 38 CHR-P, and 59 no CHR-P. 2.6% of CHR-P adolescents were adopted, 76.3% had separated-divorced parents. 34.2% of parents had a depressive disorder. Among FACES-IV sub-scale, maternal rigidity progressively increased from no-CHR-P to CHR-P to EOP group, with statistical differences between EOP and the other two groups (p=0.01). CHR-P mothers and fathers showed a high level of PSS values, without group difference. Lastly, PSS values correlated positively with the Rigidity, Disengagement and Chaos scale of FACES-IV and negatively with the Communication scale (p<0.05). Our results suggest that family functioning has a central role and could represent a worthwhile target of intervention for adolescents at CHR-P, leading the way to new preventive approaches.